Chokeberry Reduces Inflammation in Human Pre-adipocyte Cells. (14th June 2022) - Brunelle, Dale; Redvers, Nicole; Larson, Kate; Bundy, Amy; Roemmich, James; Warne, Donald
Abstract: Objectives: Chokeberry, Aronia melanocarpa, consumed as a fruit and used as a traditional food by some American Indian tribes has greater levels of anthocyanin compared to cranberries and blueberries. Animal and human studies demonstrate that chokeberry juice extract (CBE) has cardioprotective, anti-diabetic, and anti-inflammatory properties. Saturated fatty acids including palmitate (PA, 16:0) and lipopolysaccharide (LPS) produces pro-inflammatory effects by inducing inflammatory gene expression. The objective of this study was to determine the effect that CBE, Cyanidin 3-O-galactoside (C3Gal) and Cyanidin 3-glucoside(C3G) have on PA or LPS induced inflammation as measured by interleukin-6 (IL-6). Methods: Human primary subcutaneous pre-adipocyte cells (ATCC, Manassas, Virginia) were pretreated with either 2 uM C3Gal or CBE for three hours. Following pretreatment, cells were treated with 0.17 mM bovine serum albumin (BSA) for control; 0.1 mM PA; BSA in presence of 2uM C3Gal or CBE; and PA in presence of 2 uM C3Gal or CBE. RT-qPCR analysis was conducted to determine IL-6 mRNA expression normalized to 18s rRNA expression. One-way ANOVAs were run to determine significance of group differences. Results: Treatment of cells with PA increased (P < 0.0001) IL-6 mRNA compared to control and CBE groups. Treatment of cells with CBE decreased (P < 0.0001) PA-induced IL-6 mRNA while C3Gal did not (p = 0.4657). Treatment of cells with CBE decreased (P < 0.0001) LPS-induced IL-6 mRNA while C3G treatment did not (p = 0.4537). Conclusions: PA induces inflammation, as measured by IL-6 mRNA expression, in human primary subcutaneous pre-adipocyte cells. This inflammation is reduced by treatment with CBE while isolated anthocyanin such as C3- galactoside or glucoside has partial inhibition. Future studies will identify additional chokeberry anthocyanins and flavonoids important in anti-inflammatory effects. Funding Sources: This work was funded by grant support from the USDA Agricultural Research Service Project and NIH National Institute of General Medical Sciences, The Centers of Biomedical Research Excellence Award.